Perancangan ChatBot Pendaftaran Siswa Dengan Telegram BOT Design a Chatbot for Student Registration Using Telegram BOT - Harry Priambodo; Adi Muhajirin (Journal of Informatic and Information Security, 2022)
The increasing number of Covid-19 victims is making us more and more aware of the importance of health protocols from wearing masks, maintaining distance, always washing hands, avoiding crowds, etc. It was recorded that on May 19, 2022, 6 million Indonesians were confirmed positive for Covid-19, however in the new academic year SDN Sriamur 02 still applies on-site registration, and because of the increasing level of prospective students from year to year, the school admin officers are overwhelmed, from the results of initial observations. the guardians of SDN Sriamur 02, the majority of the application services used are chat services, besides being able to be used anywhere, they are also more efficient in using internet quota, therefore the author has an idea to create a bot that runs on the Telegram Messenger application that can help in the registration of prospective students, where the development model that will be used by the author is Extreme Programming which is a software development model that tries to simplify the various stages in the development process so that it becomes more adaptive and flexible, so that the Extreme Programming (XP) method puts forward adevelopment process that is more responsive to needs. The research carried out resulted in a system that was ready to be used anytime anywhere for 24 hours and succeeded in carrying out one of the protocols in the pandemic era, namely social distancing, and a dataset of prospective students stored in the Googlesheet database.